2020
DOI: 10.38141/10778/71203
|View full text |Cite
|
Sign up to set email alerts
|

Caracterización de la fracción lipídica del café verde en variedades mejoradas de Coffea arabica L.

Abstract: La fracción lipídica del grano de café, así como los compuestos que la componen, cumplen una función importante en la calidad sensorial del café. Esta investigación tuvo como objetivo caracterizar químicamente, la fracción lipídica del café verde en las variedades Tabi, Cenicafé 1 y Castillo® Naranjal, Castillo® El Tambo y Castillo® Pueblo Bello, procedentes de lotes cultivados en diferentes localidades de Colombia durante dos años de cosecha. Se determinaron los contenidos de lípidos totales, la composición d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 33 publications
0
1
0
1
Order By: Relevance
“…En café arábica de Colombia se encontraron valores de 11,1% a 16,9% (b.s.) de lípidos conformados por linoleico 39,0%, palmítico 37,0%, oleico 8,7%, esteárico 8,1%, araquídico 3,2%, linolénico 1,4% y behénico 0,8% (Villarreal, Baena, & Posada, 2012).…”
Section: Resultados Y Discusiónunclassified
“…En café arábica de Colombia se encontraron valores de 11,1% a 16,9% (b.s.) de lípidos conformados por linoleico 39,0%, palmítico 37,0%, oleico 8,7%, esteárico 8,1%, araquídico 3,2%, linolénico 1,4% y behénico 0,8% (Villarreal, Baena, & Posada, 2012).…”
Section: Resultados Y Discusiónunclassified
“…Near-infrared spectroscopy has been proposed as a tool for the identification of various quality blends of Arabic coffee [ [15] , [16] , [17] ]. It can be used to determine various components of the green bean, such as the total lipid content, the composition of fatty acids present in the lipid fraction and the content of tocopherols [ 18 ], as well as the protein content [ 19 ] and its relationship with bean origin [ 20 , 21 ] and coffee quality [ 22 ]. Furthermore, Baptista et al [ 23 ] and Correia et al [ 24 ] used NIR technology to differentiate the quality of coffee grown in association with different agroforestry species, while Silva et al [ 25 ] reported the feasibility of NIR transmittance spectra for determining the planting density of coffee trees and the maturity level of cherries.…”
Section: Introductionmentioning
confidence: 99%
“…The quality of coffee is established throughout the coffee production chain and is the result of a series of factors, such as the species and variety, the soil, the environmental conditions, and the age of the crop [9][10][11][12][13][14]. Coffee quality also depends on harvesting and postharvest processes, which include the harvesting of the fruits as well as the process used [15].…”
Section: Introductionmentioning
confidence: 99%
“…During the stages described above, the chemical compounds of the green coffee bean form and are stored; these compounds are transformed during the roasting process and express themselves when the beverage is prepared. The lipids that constitute the lipid fraction of coffee play an important role in the quality of the beverage; they are responsible for the transport of aromas and flavors [18], add body to the drink and store fat-soluble vitamins such as vitamin E [13,19] that protect or retard oxidative processes during green bean storage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation